Epimedium koreanum Nakai–Induced Liver Injury—A Mechanistic Study Using Untargeted Metabolomics - Li, Pin; Zhang, Lin; Guo, Zhaojuan; Kang, Qianjun; Chen, Cong; Liu, Xiaoyao; Ma, Quantao; Zhang, Jingxuan; Hu, Yujie; Wang, Ting (Frontiers in Pharmacology, 2022)
Epimedii Folium is widely used around the world as an herbal supplement, and the risk of induced liver damage has emerged in recent years. Our preliminary study found that among several Epimedii Folium species specified in the Chinese Pharmacopoeia, Epimedium koreanum Nakai has a more severe propensity for hepatotoxicity, but the mechanism of its hepatotoxicity has not been clarified. In this study, we explored the mechanism of hepatotoxicity of Epimedium koreanum Nakai by serum/liver tissue untargeted metabolomics. The results of experiments in vivo showed that after 28 days of exposure to Epimedium koreanum Nakai ethanol extract (EEE), the liver weight, serum AST, ALP, TBIL, etc. of the rats in the EEE group were significantly increased, and severe cytoplasmic vacuolation appeared in the liver tissue. These results suggested that EEE is hepatotoxic. Subsequently, the metabolomic revealed significant changes in the metabolic profile of rat liver and serum after exposure to EEE, in which serum metabolites such as Flavin Mononucleotide, Phenylacetylglycine, Glutathione, L-Tryptophan, and Sphingomyelin were able to accurately identify liver injury caused by EEE and be used as a serum marker to reflect EEE-induced liver injury. The KEGG pathway enrichment analysis revealed that EEE caused extensive effects on metabolic pathways in rats, with glutathione metabolism, glutamate metabolism pathway, primary bile acid biosynthesis pathway, and sphingolipid metabolism pathway, which are closely related to ferroptosis, being the most affected pathways. Then the main markers related to ferroptosis in the liver were examined. The results demonstrated that the content of malondialdehyde was significantly increased, the activity of superoxide dismutase was significantly reduced, and the ferroptosis inhibitory proteins GPX4 and System xc- were significant downregulation, while the ferroptosis-promoting protein ACSL4 was significantly upregulation. Judging from these results, we can conclude that the mechanism of hepatotoxicity of Epimedium koreanum Nakai is probably related to the induction of ferroptosis in hepatocytes.